2019
DOI: 10.1073/pnas.1804013116
|View full text |Cite
|
Sign up to set email alerts
|

Activation of PASK by mTORC1 is required for the onset of the terminal differentiation program

Abstract: During skeletal muscle regeneration, muscle stem cells (MuSCs) respond to multiple signaling inputs that converge onto mammalian target of rapamycin complex 1 (mTORC1) signaling pathways. mTOR function is essential for establishment of the differentiationcommitted progenitors (early stage of differentiation, marked by the induction of myogenin expression), myotube fusion, and, ultimately, hypertrophy (later stage of differentiation). While a major mTORC1 substrate, p70S6K, is required for myotube fusion and hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 42 publications
4
35
0
Order By: Relevance
“…Ablation of 4EBP1 facilitates myofiber growth, but does not affect the activation of satellite cells [137]. After injury, activation of Per-Arnt-Sim domain kinase (PASK), a downstream phosphorylation target of mTORC1, phosphorylates Wdr5 to induce the expression of myogenin and stimulates MuSCs differentiation into myoblasts [138] (Figure 3C). The mTORC1-S6K pathway is also required for myoblasts fusion to accomplish myofiber formation during muscle regeneration [138].…”
Section: Roles Of Mtor In Skeletal Muscle Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ablation of 4EBP1 facilitates myofiber growth, but does not affect the activation of satellite cells [137]. After injury, activation of Per-Arnt-Sim domain kinase (PASK), a downstream phosphorylation target of mTORC1, phosphorylates Wdr5 to induce the expression of myogenin and stimulates MuSCs differentiation into myoblasts [138] (Figure 3C). The mTORC1-S6K pathway is also required for myoblasts fusion to accomplish myofiber formation during muscle regeneration [138].…”
Section: Roles Of Mtor In Skeletal Muscle Regenerationmentioning
confidence: 99%
“…After injury, activation of Per-Arnt-Sim domain kinase (PASK), a downstream phosphorylation target of mTORC1, phosphorylates Wdr5 to induce the expression of myogenin and stimulates MuSCs differentiation into myoblasts [138] (Figure 3C). The mTORC1-S6K pathway is also required for myoblasts fusion to accomplish myofiber formation during muscle regeneration [138]. micro-RNAs (miRNAs) have been reported as important modulators of myoblasts formation and fusion during muscle regeneration [139,140,141,142].…”
Section: Roles Of Mtor In Skeletal Muscle Regenerationmentioning
confidence: 99%
“…Both mTORC1 and mTORC2 regulate cellular metabolism, survival, proliferation, and growth. mTORC1 is a central hub for nutrient-sensing and energy metabolism and, as such, coordinates anabolic protein and nucleotide synthesis and catabolic autophagy 9 16 . On the other hand, mTORC2 drives insulin signaling by phosphorylating Akt ( Ser473 )/PKB downstream of the phosphoinositide 3-kinase (PI3K)/insulin pathway 17 20 .…”
Section: Introductionmentioning
confidence: 99%
“…( 6‐12 ) PASK is posttranslationally activated in response to nutrient and hormonal signals by phosphorylation by the mammalian target of rapamycin complex 1 (mTORC1) protein kinase. ( 13 ) Finally, PASK is also regulated by metabolic status at the level of gene expression. ( 7 ) Studies using genetic and pharmacologic approaches have further demonstrated that PASK is required for the proteolytic maturation in mouse and rat liver of sterol regulatory element‐binding protein (SREBP)‐1c, a transcriptional activator of genes that encodes the enzymes that catalyze fatty acid and triglyceride (TG) production.…”
mentioning
confidence: 99%